Nutrigenomic underpinnings of intestinal stem cells in inflammatory bowel disease and colorectal cancer development - Ho, Jennifer; Puoplo, Nicholas; Pokharel, Namrata; Hirdaramani, Aanya; Hanyaloglu, Aylin C.; Cheng, Chia-Wei (Frontiers in Genetics, 2024)
Food-gene interaction has been identified as a leading risk factor for inflammatory bowel disease (IBD) and colorectal cancer (CRC). Accordingly, nutrigenomics emerges as a new approach to identify biomarkers and therapeutic targets for these two strongly associated gastrointestinal diseases. Recent studies in stem cell biology have further shown that diet and nutrition signal to intestinal stem cells (ISC) by altering nutrient-sensing transcriptional activities, thereby influencing barrier integrity and susceptibility to inflammation and tumorigenesis. This review recognizes the dietary factors related to both CRC and IBD and investigates their impact on the overlapping transcription factors governing stem cell activities in homeostasis and post-injury responses. Our objective is to provide a framework to study the food-gene regulatory network of disease-contributing cells and inspire new nutrigenomic approaches for detecting and treating diet-related IBD and CRC.